2015
DOI: 10.3758/s13414-015-0986-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual grouping of objects occupied by target and flankers affects target-flanker interference

Abstract: We report four experiments that tested whether object-based attentional spreading can be modulated by the perceptual structure of objects occupied by target and flankers in a flanker task. The target and flankers were presented on a single object or three separate objects (of same or different shape), displayed at fixed, known locations. The flanker compatibility effect was larger when the target and flankers were on the same object or on three objects of the same shape than when they were on three objects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(113 reference statements)
2
18
1
Order By: Relevance
“…They found that when the attentional scope was broadened, attention went more frequently to the location of the salient colour singleton, but when the attentional scope was narrowed, attention went to the location of the salient colour singleton just as frequently as other elements in the display, indicating that the size of attentional scope played an important role in attentional selection. Therefore, with a broadened attentional scope, wholist individuals preferred to group the two objects as one unit, so attentional resources were spread equally to the two invalid locations within the object’s boundaries, leading to the disappearance of object-based effects, which was in line with the study of Luo and Proctor (2016). With a narrowed attentional scope, analytic individuals tended to perceive the two objects as independent objects, so attentional resources were spread within the cued object’s boundaries, resulting in the occurrence of object-based effects.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…They found that when the attentional scope was broadened, attention went more frequently to the location of the salient colour singleton, but when the attentional scope was narrowed, attention went to the location of the salient colour singleton just as frequently as other elements in the display, indicating that the size of attentional scope played an important role in attentional selection. Therefore, with a broadened attentional scope, wholist individuals preferred to group the two objects as one unit, so attentional resources were spread equally to the two invalid locations within the object’s boundaries, leading to the disappearance of object-based effects, which was in line with the study of Luo and Proctor (2016). With a narrowed attentional scope, analytic individuals tended to perceive the two objects as independent objects, so attentional resources were spread within the cued object’s boundaries, resulting in the occurrence of object-based effects.…”
Section: Discussionsupporting
confidence: 60%
“…However, analytic individuals were expected to process detailed information step by step and focus on the subset of the whole at the same time. Moreover, in Luo and Proctor’s (2016) study, when three small objects were grouped into a large object unit, the object-based effect disappeared. Hence, we predicted that an object-based effect could only be obtained for analytic individuals, but not for wholist individuals.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the Gestalt law of perceptual organization by similarity (Hartmann, 1935;Wagemans et al, 2012), stimuli with similar physical properties (e.g., same color) tend to be grouped. In the flanker task, congruency effects are larger when targets and distractors are perceptually grouped on the basis of similarity than when they are not (Baylis & Driver, 1992;Harms & Bundesen, 1983;Kramer & Jacobson, 1991;Luo & Proctor, 2016). The main explanation of this finding is that dissimilar stimuli (e.g., targets and distractors in different colors) are easier to visually parse than are similar stimuli, improving selective attention to the target and reducing distractor influence.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, breaking up such a grouping may lead to a “reemergence” of the CSPC effect. Importantly, investigating this issue not only may extend Gestalt principles to the domain of cognitive control (cf, Luo & Proctor, 2016), and to a paradigm in which stimuli never appear concurrently, but it also offers a fruitful avenue for exploring a prominent account of CSPC effects, the episodic retrieval account , which we introduce next.…”
mentioning
confidence: 99%